USAGE OF GRAMMATICAL STRUCTURES IN COMMUNICATION. ("Conference on Universal Science Research 2023", 2023)
The main general educational standard for foreign language is quality in foreign language learning sets tasks to achieve new goals, in particular: its components - speech, development of linguistic, socio-cultural, foreign language communicative compensatory and educational and cognitive. It is known that the communicative process of learning building, first of all, modeling the situation as a communication unit and its activity. This article provides information about Usage of grammatical structures in communication